Psychotic symptoms in a patient with Systemic Lupus Erythematosus: A diagnostic dilemma between lupus psychosis and steroid induced psychosis. (December 2022) - Pathak, Bishnu Deep; Regmi, Binit Upadhaya; Dhakal, Bishal; Joshi, Sushil; Simkhada, Nabin; Sapkota, Suhail; Joshi, Sushant; Thapa, Sujan Rana
Abstract: Introduction: Systemic Lupus Erythematosus (SLE) is a chronic auto-immune disorder with the involvement of multiple organ systems. It is more common in females. Case presentation: Here, we present a case of 12-year-old female, known case of SLE with lupus nephritis, presenting with neuropsychiatric symptoms. She was under steroids as well for a few weeks due to flare-up of symptoms prior to that. Due to this, there was a diagnostic dilemma between lupus psychosis and steroid induced psychosis. Clinical discussion: Approximately one third to half of the patients may have neurological involvement in Systemic Lupus Erythematosus. However, neuropsychiatric symptoms in them could be due to corticosteroids, which are frequently used in treatment. There are no definitive and easily available laboratory markers to distinguish these two aetiologies. Conclusions: Systemic Lupus Erythematosus patients, who are on steroids, with neuropsychiatric features should be assessed adequately. As there are no specific guideline and biomarkers to distinguish between these two, meticulous evaluation is necessary for appropriate management. Highlights: In SLE, neuropsychiatric manifestations can be due to disease itself or drugs used to treat it. It is very difficult to distinguish lupus induced psychosis from steroid induced psychosis. There are no any definitive investigations or guidelines to differentiate between the two. However, risk factors like lupus nephritis, hypoalbuminemia and female sex help to separate them. Whatever may be the cause for the psychotic symptoms, it should be evaluated first and treated with anti-psychotics.